2012
DOI: 10.1021/tx300002q
|View full text |Cite
|
Sign up to set email alerts
|

Protein Carbonylation in a Murine Model for Early Alcoholic Liver Disease

Abstract: Hepatic oxidative stress and subsequent lipid peroxidation are well-recognized consequences of sustained ethanol consumption. The covalent adduction of nucleophilic amino acid side-chains by lipid electrophiles is significantly increased in patients with alcoholic liver disease (ALD); a global assessment of in vivo protein targets and the consequences of these modifications, however, has not been conducted. In this report, we describe identification of novel protein targets for covalent adduction in a 6-week m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
100
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(103 citation statements)
references
References 44 publications
3
100
0
Order By: Relevance
“…In 2012, Curtis et al (52) undertook a proteomics study in which they identified over 200 mitochondrial targets of protein In addition to obesity, elevated protein carbonylation has been observed in human and mouse models of neurodegenerative disease, cardiovascular disease, diabetes, cancer, hepatosteatosis, asthma, and pulmonary disease. including 4HNE, 4ONE, and acrolein modification sites (71). Consistent with the observed mitochondrial dysfunction and lipid accumulation characteristics of this disease model, bioinformatic pathway analysis revealed that fatty acid metabolism, oxidative phosphorylation, glycolysis, and drug metabolism were among the top modified pathways.…”
Section: Lipid Peroxidation and Apoptosissupporting
confidence: 76%
“…In 2012, Curtis et al (52) undertook a proteomics study in which they identified over 200 mitochondrial targets of protein In addition to obesity, elevated protein carbonylation has been observed in human and mouse models of neurodegenerative disease, cardiovascular disease, diabetes, cancer, hepatosteatosis, asthma, and pulmonary disease. including 4HNE, 4ONE, and acrolein modification sites (71). Consistent with the observed mitochondrial dysfunction and lipid accumulation characteristics of this disease model, bioinformatic pathway analysis revealed that fatty acid metabolism, oxidative phosphorylation, glycolysis, and drug metabolism were among the top modified pathways.…”
Section: Lipid Peroxidation and Apoptosissupporting
confidence: 76%
“…n ϭ 6 mice/group. (MDA), and acrolein are all increased by chronic ETOH consumption after 6 weeks, these effects have not been characterized after 7.5 weeks of ETOH consumption (48). From Fig.…”
Section: Table 1 Liver Parameters Obtained From Pair-fed and Etoh-fedmentioning
confidence: 89%
“…As a major indicator of oxidative stress and inflammation, 4-HNE is proposed to simultaneously initiate cellular damage as well as promote cellular survival (53). Recent proteomic studies have identified numerous protein targets of 4-HNE in cell culture as well as in a murine model of early ALD (48,54). In cells, concentrations of 4-HNE are highest within membranes with calculated hepatocellular concentrations in CCl 4 -and BrCCl 3 -treated rats of 3.8 and 11.3 mM, respectively (8,55,56).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas the animal model used for this current investigation does replicate early ALD, encompassing steatosis and oxidative stress ( 12,13,20 ), it does not encompass progression from the steatosis to steatohepatitis, which would occur using more prolonged ethanol administration paradigms ( 42 ). The present report presents novel data describing the response of L-FABP Ϫ / Ϫ mice to the sustained ingestion of ethanol for six weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Protein collected from cytosolic fractions was derivatized with biotin hydrazide and stabilized with sodium borohydride as previously described ( 20 ). Samples were denatured, separated via standard SDS-PAGE, and visualized with an anti-biotin antibody (GeneTex, Irvine, CA).…”
Section: Biotin Hydrazide Derivatization Of Protein Carbonylsmentioning
confidence: 99%